Community Response to the Cultural Da’wah Practices by Muhammadiyah Preachers in Palembang City - Wijaya, Idmar; Romli, Romli; Azwar, Alfi Julizun (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to analyze the community's response to the practice of cultural da'wah by Dai Muhammadiyah in Palembang City. The research approach used is qualitative, descriptive-exploratory. The informants were community leaders, religious leaders, Muhammadiyah members and Muhammadiyah leaders. Data collection methods use observation, in-depth interviews, and documentation. This research concludes that first, the concept of cultural da'wah from Muhammadiyah's perspective is none other than that Muhammadiyah uses culture as a medium for da'wah, thus the concept of cultural da'wah is based on: a) friendly, b) polite, c) courteous, d) civilized, e) tolerance, f) not hate, g) educate, and h) help. Second, the implementation of Dai Muhammadiyah's cultural da'wah is principally through existing local cultural forms such as kenduri culture, thanksgiving, recitation in the community, Islamic holidays, nasyid art, the art of reading the Koran, calligraphy, martial arts, and the art of archery. Third, the public's response to the cultural da'wah practices carried out by Dai Muhammadiyah, both from community leaders, religious leaders, Muhammadiyah residents and Muhammadiyah leaders, on average they responded quite well because Dai Muhammadiyah when giving his lectures did not touch on furu'iyah issues, did not demean the congregation and seeks to educate society and Dai Muhammadiyah gives lectures based on arguments and rationality. And fourth, the reason for acceptance is because Dai Muhammadiyah is rational in the material presented, it is also based on propositions and there is rhetoric, on average the material presented is actual. For those who reject it on the grounds that if culture and religion are mixed, they are worried that syncretism will occur because preaching is firm, straightforward and clearly does not need to compromise with the culture of society, saying that what is right is right and what is false is false.